Road safety: factors influencing young driver behaviour among UUM students - Rosli, Nor Hidayah; Mohd Rani, Nor Fatin Najwa; Mustaffa, Siti Hajartul; Abdul Hanan, Suhaila (2017)
The contribution of risky behavior towards road accident and fatality among young drivers has been highlighted in the many road safety literatures. In Malaysia, the number of road accidents has increased every year.Among the road accident victims, young drivers contribute the highest rate of fatalities and injuries.The objective of the study is to examine the relationship between gender, license type and road crash involvement with young driver behavior.Therefore, the Behaviour of Young Novice Drivers Scale (BYNDS) has been utilized in this study.The Reciprocal Determinism Model (RDM) by Albert Bandura has been used as underpinning theory to understand driver behaviour.350 respondents participate in this research and all of them have experience driving a car.The result of the finding showed there was a significant difference between male and female drivers toward young driver behavior. However, the result for the license types and road crash involvement is not significant and it shows that this variable not related to young driver behavior.The recommendations for road safety intervention and future research have also been addressed.